The absent presence: Children's place in narratives of human trafficking. Issue 2 (8th July 2018) - Blazek, Matej; Esson, James
Abstract : This paper uses in‐depth qualitative data, obtained as part of research examining human trafficking from Slovakia to the United Kingdom, to explore the place of children in human trafficking processes. Rather than foregrounding cases of children as direct subjects of abuse, the paper focuses on instances where children are used to control, manipulate and exploit relatives embroiled in human trafficking. We study examples when children are moved across national borders and those when they remain in the home country, and show how in both accounts their (absent) presence constitutes a significant means for facilitating, maintaining and intensifying the exploitation of their adult relatives. Through doing so, the paper demonstrates how identifying the distinct spaces and moments within which children appear in narratives of exploitation has the potential to uncover nefarious practices occurring within the human trafficking process, as well as the indirect effects of human trafficking on family dynamics. The paper extends conceptual understandings of agency in human trafficking by illustrating how children are simultaneously subjects of exploitation and emplaced through complex channels within the exploitation of others.